Kawalan mikrokomputer ke atas motor pelangkah dan simulasinya - Mahamod Ismail,; Ismail,Mohd. Alauddin Mohd. Ali,; Kam , Teik Boon (1991)
SMOC system (Stepper Motor Controller) has been designed to control a stepper motor using a microcomputer. 7he system consists of Automatic Control Mode, Position Control Mode, Keyboard Control Mode, Timer Control Mode and other facilities like DOS System, Help Menu and Data Files. 7his package is menu oriented and developed using Turbo basic languagefor IBM PCIA Tcomputer. IBM PCIA T'S parallel printer port has been used to interface with the motor's power driver circuit which is specially designedfor this project. Controlled data such as the motor's speed, the direction of rotation, the current step number, the total steps number, the status of the motor as well as the speed indicator and the motor stepping simulation will be displayed on the screen